Comparison of Reticulocyte Hemoglobin Equivalent Levels between Low and Normal Birth Weight Newborns - Resvi Livia; Fajar Wasilah; Leni Lismayanti (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Low Birth Weight (LBW) newborns face a risk of iron deficiency. Iron deficiency hinders growth, and motoric, and cognitive development. Newborns with LBW sometimes suffer from inflammation, which affects the commonly used iron measurements. Reticulocyte hemoglobin equivalent (Ret-He) is considered a potential tool to measure iron profile because it measures functional iron, and it is not affected by inflammation. This study compared the Ret-He in LBW and normal birth weight newborns. This cross-sectional study was done retrospectively by observing and comparing the hematology data of newborns from November to December 2019. The difference in Ret-He level was assessed using a non-parametric test. Out of 70 newborns, 26 were normal and 44 were LBW. The proportion of LBW newborns with anemia was higher than the proportion of normal ones (29.6% vs 7.7%, p=0.03). The median value of Ret-He in LBW was lower compared to normal birth weight (32.6 vs 33.3 pg, p=0.09), however, the values were still within the normal limits. Five from 70 of these newborns' Ret-He levels were under the reference range (7.14%). There was found that CRP levels were higher in LBW newborns than normal ones (5.6% vs 5%, p=0.98). There was a positive correlation between Ret-He and the birth weight of the newborns (r= 0.34, p =<0.01). There was no significant difference in Ret-He levels of LBW compared to normal babies. Further research is needed with a larger sample size to better assess the association of Ret-He and iron profiles in newborns.